Thermal analysis of the synergistic influence of the organic and mineral constituents of biomass on coal and biomass fuel blends - Oladejo, Jumoke Mojisola (2018)
Energy security, affordability and availability, as well as ensuring environmental sustainability are crucial considerations necessary for determining the future energy mix. The forecasted continuous use of coal in power generation and chemical industries makes it an important, yet polluting energy source. This has motivated researchers into investigating various clean coal processes such as the increased interest in co-blending of coal with alternative fuels like biomass due to its carbon lean nature. However, the utilisation of coal and biomass blends in conventional thermal reactors has high potential of operational challenges associated with the differences in the physical and chemical characteristics of coal in comparison to biomass. Moreover, the differences in these fuels’ properties have been studied and concluded to lead to synergy in fuel blends reactions. Synergy in fuel blends are interactions between the biomass and coal samples that results in non-additive improvement in the experimental outcome of the thermal reaction in comparison to the additive expectation from both contributing fuels. In order to improve the uptake of such fuel blends in power plants, a clear knowledge and understanding of the fuel blends thermal behaviour is essential. There is, therefore, a need to develop suitable and efficient characterisation technique for coal and biomass blends so that their combustion performance such as optimal operating temperatures and burnout temperatures can be predicted more effectively especially relating to the cause and degree of synergy observed in such fuel blends. In this work, a series of experiments were conducted for the thermal characterisation of two coal samples (Guizhou and Yunnan coal) and three biomass samples (oat straw, rice husk and spruce wood) and their fuel blends during combustion reaction. The thermal analysis was carried out using a thermogravimetric analyser. The influence of biomass organic and inorganic constituents on coal samples during the co-blending reaction, especially the synergy influence on the char oxidation reaction has been investigated. This was to study the catalytic and non-catalytic mode of synergy. This was done by blending of coal samples with biomass ash, demineralised biomass, simulated biomass and potassium impregnated biomass samples. In addition, the quantification of the degree of synergy interaction observed was done by formulating a synergy index. Finally, the effect of such interactions in coal and biomass blends gasification was also investigated. The observations in the results included substantial decrease in the peak temperature, burnout temperature and activation energy of the char oxidation stage of most of the fuel blends. This is representative of the non-additive interaction between the coal and biomass samples and was detected in both catalytic and non-catalytic mode of synergy in varying extent. The catalytic mode of synergy are all improvements associated with the inorganic content of biomass, mostly the alkali and alkaline earth metals while the non-catalytic synergy is resulting from the organic content of biomass. During the non-catalytic mode of synergy, the deviation in the char reaction zone and its characteristic temperatures remained similar for all blend ratios, and does not vary significantly with increase in biomass blending ratio. However, the influence of hydrogen donation from the biomass volatiles increases the reactivity significantly especially relating to reaction time and burnout. In contrast, the disparity in the peak and burnout temperature associated with catalytic synergy increased rapidly with biomass blend ratio, indicating a multiplying influence of the catalysing alkali and alkali earth metals (AAEMs). Additionally, the extent of synergistic deviation was also dependent on coal’s constituents such that Guizhou coal revealed the least degree of both synergy modes. This is associated with its with high hydrogen – to –carbon ratio which minimise the interactive influence from biomass hydrogen donation and its high ash content which has potential for deactivating catalytic inorganic elements. The results of this research show that at 50wt% biomass blend ratio, Yunnan coal and oat straw shows the highest synergy while Yunnan coal and rice husk remained additive in behaviour. In addition to this, a degree of synergy inhibition and promotion was observed between the two modes of synergy such that Yunnan coal blends which high catalytic and high non-catalytic synergistic interaction had revealed only 6.1 – 73.8% combined synergy efficiency. The synergy efficiency measures the degree of competition or promotion between the catalytic and non-catalytic synergy modes during the thermal reaction. Whereas Guizhou coal which had insignificant and moderate indication of synergy with organic and inorganic elements of biomass respectively showed up to 1.4 and 5 times multiple of the expected combined synergy. This was resulting from the somewhat overlapping functions of both synergy modes. Lastly, the difference in the efficacy of different biomass inorganic elements during high temperature gasification was observed in the coal and biomass fuel blends. The result obtained indicated that blends with calcium – rich spruce wood revealed negligible improvement compared to potassium rich oat straw due to their restricted mobility on the char surface and their deactivation at higher temperatures >900°C by forming thermally stable calcium oxide. The increase in micro-porosity of the blended fuel’s char was also observed. These fundamental results have provided insights into coal and biomass co-blending behaviour during co-firing and gasification that can be used in aiding the design considerations and optimising the biomass blending ratio to ensure appropriate operation of co-fired fuel reactors. The result revealed that in this study, synergy was highest in the Yunnan coal and oat straw blends at 50:50wt% ratio. This was resulting from the potassium - rich nature of oat straw and low hydrogen content of Yunnan coal, making it a viable proton acceptor in both catalytic and non-catalytic synergy reactions.